Value of diffusion-weighted MR imaging in the diagnosis of lymph node metastases in patients with cholangiocarcinoma - Holzapfel, Konstantin; Gaa, Jochen; Schubert, Elaine C.; Eiber, Matthias; Kleeff, Jörg H.; Rummeny, Ernst-Josef; Loos, Martin (Abdominal radiology, 2016)
Cholangiocarcinoma, Lymph node metastases, MR imaging, Diffusion-weighted MR imaging (DWI)